2008 Workshop on High Performance Computational Finance 2008
DOI: 10.1109/whpcf.2008.4745400
|View full text |Cite
|
Sign up to set email alerts
|

FPGA acceleration of mean variance framework for optimal asset allocation

Abstract: Asset classes respond differently to shifts in financial markets, thus an investor can minimize the risk of loss and maximize return of his portfolio by diversification of assets. Increasing the number of diversified assets in a financial portfolio significantly improves the optimal allocation of different assets giving better investment opportunities. However, a large number of assets require a significant amount of computation that only high performance computing can currently provide. Because of the highly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…More recently, hardware accelerators with multi-core and many-core processors are employed. For example, financial risk applications are accelerated on Cell BE processors [13,14], FPGAs [15,16] and GPUs [17,18].…”
Section: Related Workmentioning
confidence: 99%
“…More recently, hardware accelerators with multi-core and many-core processors are employed. For example, financial risk applications are accelerated on Cell BE processors [13,14], FPGAs [15,16] and GPUs [17,18].…”
Section: Related Workmentioning
confidence: 99%
“…For example, research related to financial applications exploiting the Cell BE processor is reported in [32,33]. FPGAs are another alternative platform presented in [34,35,36,37]. GPU acceleration is employed more recently [38,39,40,41].…”
Section: Related Workmentioning
confidence: 99%
“…Another option for acceleration is to use Maxeler acceleration cards running dataflow engines on FPGAs (see [22], [23] and [24] for examples of accelerating Monte Carlo with FPGAs, and [25] for other examples of financial computation accelerated with FPGAs). This case study is only a simple example of running a single model repeatedly, while real world applications are likely to be much more complicated, it has been shown in [2] and [22] that FPGAs are appropriate for scaling up to large scale risk computations.…”
Section: Acceleration Of the Monte Carlo Case Studymentioning
confidence: 99%